2017
DOI: 10.1088/1741-4326/aa94f0
|View full text |Cite
|
Sign up to set email alerts
|

Helium retention in krypton ion pre-irradiated nanochannel W film

Abstract: Nanochannel tungsten (W) film is a promising candidate as an alternative to bulk W for use in fusion applications. In previous work it has been shown to have good radiation resistance under helium (He) irradiation. To further understand the influence of the irradiationinduced displacement cascade damage on helium retention behaviour in a fusion environment, in this work, nanochannel W film and bulk W were preirradiated by 800 keV Kr 2+ ions to the fluence of 2.6 × 10 15 ions cm −2 and subsequently irradiated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…However, different phenomena were shown on the synergistic irradiated bulk W. No blister appeared on the bulk W surfaces when the subsequently irradiated He fluence was 3 × 10 17 ions•cm −2 . With continuously increasing of the He fluence to 5 × 10 17 ions•cm −2 , the size and density of blisters formed on the bulk W decreased significantly compared with those of individual He + ions irradiated bulk W at the same fluence [39]. These results show that the pre-irradiated Kr 2+ ions can effecitvely inhibit the formation of surface blistering.…”
Section: Synergistic Irradiations Of He + and Kr 2+ Ionsmentioning
confidence: 75%
See 1 more Smart Citation
“…However, different phenomena were shown on the synergistic irradiated bulk W. No blister appeared on the bulk W surfaces when the subsequently irradiated He fluence was 3 × 10 17 ions•cm −2 . With continuously increasing of the He fluence to 5 × 10 17 ions•cm −2 , the size and density of blisters formed on the bulk W decreased significantly compared with those of individual He + ions irradiated bulk W at the same fluence [39]. These results show that the pre-irradiated Kr 2+ ions can effecitvely inhibit the formation of surface blistering.…”
Section: Synergistic Irradiations Of He + and Kr 2+ Ionsmentioning
confidence: 75%
“…Ion beam irradiation with many advantages such as flexible irradiation conditions is considered as an effective method to simulate the neutron irradiation, although there are some differences with the neutron irradiation [38]. Using the high-energy heavy ions irradiation (800 keV krypton (Kr 2+ )) to simulate the displacement cascade damage induced by the neutron irradiation, the displacement damage influence on the He retention in nanochannel W film was further studied [39].…”
Section: Synergistic Irradiations Of He + and Kr 2+ Ionsmentioning
confidence: 99%
“…From the above analysis, it can be seen that the shift tendency of each peak under different damage conditions was different, which means that its ability to resist He + ion irradiation was different. Referring to Figure 3, it can be considered that the left-shift of the diffraction peak was produced due to the lattice swelling induced by He bubbles, while the subsequent right-shift of the peaks in SGs was mainly due to the stress relaxation induced by crack formation, as shown in the TEM image [26,27]. For the LGs, although the cracks formed under high He concentration, this did not affect the continued swelling of the monoclinic grains (peak {111} m ), which may have been due to the large grain size preventing the release of He in time.…”
Section: Resultsmentioning
confidence: 99%
“…Under the irradiation of high temperature and high beam He plasma at more than 5000 s, only tungsten in the range of 72 nm from top surface is transformed into fuzz structure in nanochannel thin films, while the surface of irradiated bulk tungsten alloy would be seriously eroded. The result indicated the effectively relieve thermal stress and maintain resistance to the He nucleation and "fuzz" formation behavior of nanochannel structure under high-temperature irradiation [115,116]. The previous work [112] has shown that {100} surface in tungsten might own better resistance to morphology change due to the larger binding energy.…”
Section: Nanochannel Tungsten Enhances Radiation Tolerancementioning
confidence: 88%